Scenario Planning of Digital Transformation in Indonesia’s Fast-Moving Consumer Goods Sales Organization: Uncertainties and Possibilities - Kusuma, Adhitya Rendra; Syarief, Rizal; Ekananta , Arry; Sukmawati, Anggraini (Bina Nusantara University, 2023)
Since uncertainty in the business domain has increased the urgency for scenario development as a strategic tool, the research examined a relationships between a leadership model, organizational citizenship behavior, and sales management control variables using scenario planning. The questionnaire’s scaling using a Likert scale was done toward results from discussions and in-depth interviews with several experts in Fast-Moving Consumer Goods (FMCG) organizations, FMCG organizational leaders (Chief Executive Officers/CEOs), leadership experts, organizational behavior consultants, and organizational performance practitioners. The research finds that external and internal forces determine the success of digital transformation. External forces consist of digital technology availability, consumer expectations,business competition maps, and digital talents. Internal forces are budget allocation, competency trap versus growth mindset, organizational structure, and organizational culture. The scenario matrix plot forms four scenarios of the digital transformation in the sales organization of Indonesia’s FMCG companies (realistic, pessimistic, optimistic, and superoptimistic), where realistic (iteration improvement scenario) is largely predicted to occur for companies carrying out digital transformation. Such scenario requires sales organizations to have a growth mindset to deal with the uncertainty of customer/consumer expectations properly. The strategy appearing as an FMCG digital transformation compass is expected to advise FMCG companies in Indonesia when executing and overseeing the digital transformation within theircompanies.